2022
DOI: 10.1007/s11104-022-05536-9
|View full text |Cite
|
Sign up to set email alerts
|

Paraburkholderia atlantica is the main rhizobial symbiont of Mimosa spp. in ultramafic soils in the Brazilian Cerrado biome

Abstract: were characterized for their nodulation capacity on M. pudica and common bean, and their tolerance to Ni in culture medium. Bacteria were also partially identified by their 16S rRNA gene sequences. In addition, recA, gyrB, nodC and nifH genes from five representative isolates were sequenced for phylogenetic studies. Results In situ detection indicated the exclusive presence of Paraburkholderia sp. within the nodules. This identification was confirmed for most of the isolates by the analysis of their 16S rRNA g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
0
0
0
Order By: Relevance
“…Paraburkholderia caribensis was first reported to be a symbiont of Mimosa in Taiwan by Chen et al (2003a), but the (non-symbiotic) type strain MWAP64 T was isolated originally from soils in Martinique (Achouak et al 1999); since then, P. caribensis has been isolated from nodules of invasive Mimosa species in various locations in Asia, such as China (Liu et al 2020), but this is the first report of it as a symbiont of Mimosa in Brazil. Similarly, P. phenoliruptrix was originally isolated from a chemostat (Coenye et al 2004) and then revealed to be related to a symbiont of M. flocculosa in Brazil, as represented by Burkholderia strain BR3462 (Chen et al 2005a), which was later formally described as P. phenoliruptrix strain BR3459a (Cunha et al 2012), and which like BR3614 (this study), possesses P. phymatum -type nod and nif genes (Soares-Neto et al 2022). Thereafter, P. phenoliruptrix has been quite frequently isolated as a nodulating symbiont of native Mimosa and Calliandra species in Brazil, and with widely varying nod and nif genes (this study), but also of introduced species like Acacia decurrens (Zilli et al 2021; this study).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Paraburkholderia caribensis was first reported to be a symbiont of Mimosa in Taiwan by Chen et al (2003a), but the (non-symbiotic) type strain MWAP64 T was isolated originally from soils in Martinique (Achouak et al 1999); since then, P. caribensis has been isolated from nodules of invasive Mimosa species in various locations in Asia, such as China (Liu et al 2020), but this is the first report of it as a symbiont of Mimosa in Brazil. Similarly, P. phenoliruptrix was originally isolated from a chemostat (Coenye et al 2004) and then revealed to be related to a symbiont of M. flocculosa in Brazil, as represented by Burkholderia strain BR3462 (Chen et al 2005a), which was later formally described as P. phenoliruptrix strain BR3459a (Cunha et al 2012), and which like BR3614 (this study), possesses P. phymatum -type nod and nif genes (Soares-Neto et al 2022). Thereafter, P. phenoliruptrix has been quite frequently isolated as a nodulating symbiont of native Mimosa and Calliandra species in Brazil, and with widely varying nod and nif genes (this study), but also of introduced species like Acacia decurrens (Zilli et al 2021; this study).…”
Section: Discussionmentioning
confidence: 84%
“…A significant difference between central Brazil and central Mexico is that soils are highly acidic in the former (dos Reis Junior et al 2010) and neutral-alkaline in the latter (Bontemps et al 2016). Low soil pH is a known factor in promoting the occurrence of acid-tolerant Paraburkholderia (Stopnisek et al 2014) as symbionts in both the main centers of Beta-rhizobial diversity, central Brazil and the CCR of South Africa (Garau et al 2009;Howieson et al 2013;Lemaire et al 2015Lemaire et al , 2016Pires et al 2018), especially when combined with low soil fertility (Elliott et al 2009;Pires et al 2018;Soares-Neto et al 2022).…”
Section: Factors Driving Beta-rhizobial Diversity In Brazilmentioning
confidence: 99%
See 1 more Smart Citation